Study on the selective oxidation of methane over highly dispersed molybdenum-incorporated KIT-6 catalysts. Issue 12 (12th May 2021) - Chen, Pei; Xie, Zean; Zhao, Zhen; Li, Jianmei; Liu, Bonan; Liu, Baijun; Fan, Xiaoqiang; Kong, Lian; Xiao, Xia
Abstract : The isolated MoO x species contribute to the highly selective formation of formaldehyde. Abstract : A series of molybdenum-incorporated mesoporous silica (Mo–KIT-6) catalysts were successfully synthesized by a one-pot hydrothermal synthesis method, and were applied in the selective oxidation of methane to formaldehyde using oxygen as an oxidizing agent under atmospheric pressure. Comparatively, the corresponding supported catalysts (Mo/KIT-6) were prepared by incipient-wetness-impregnation method. The results of the small angle XRD, nitrogen adsorption/desorption isotherms, UV-vis, H2 -TPR and UV-Raman spectroscopy characterization combined with the catalytic activity tests demonstrated that molybdenum atoms were inserted into the framework of the mesoporous materials for the Mo–KIT-6 catalysts and the highly dispersed MoO bonds dominantly existed, which were responsible for the efficient selective formation of formaldehyde. However, for Mo/KIT-6 catalysts, the molybdenum oxide species were mainly loaded on the surface or inside the outer pore channels of the support and abundant emergence of the Mo–O–Mo bond played a major role in the activation of methane to CO x . Furthermore, with equivalent molybdenum content, the methane selective oxidation performance of 8Mo–KIT-6 was obviously better than that of 4.6Mo/KIT-6, and the formaldehyde yield (2.1%) of 8Mo–KIT-6 was 2.3 times as much as that (0.9%) of 4.6Mo/KIT-6. In situ and operando UV-Raman results demonstrated that the structures of the MoO x active sites have a strong effect on the formation and elimination of carbon deposition during the separated redox reaction with methane and O2, respectively. The polymerized MoO x active sites are favorable for the formation of graphitic carbon (G), which is called ordered carbon, while the isolated MoO x active sites are favorable for the formation of disordered carbon (D). The reduced highly dispersed MoO x active sites incorporated in the framework of silica are more easily reoxidized than those on the supported catalysts.